Fiscal consolidation under market's scrutiny: How do fiscal announcements affect bond yields - Josef Švéda; Jaromír Baxa; Adam Geršl (Charles University in Prague, Institute of Economic Studies (IES), 2022)
We estimate the short-run reactions of bond spreads of selected EU member states vis-à-vis the German bund on fiscal announcements from January 2000 till December 2019. To avoid selection bias, the announcements are scrapped from the Factiva database, and then, depending on their tone, they are classified as hawkish or dovish. We show that announcements of fiscal consolidation decrease the spreads-however, the full-sample result masks substantial time and country variation. The impact of fiscal consolidation is statistically significant, namely in the post-crisis period since the Draghi's "whatever it takes" speech, but not before the Great Recession or during the European Debt Crisis.
Keywords: E62; G01; G12; 330; fiscal announcements; bond spreads; EU debt crisis; fiscal consolidation